Quantifying regional sea level rise contributions from the Greenland Ice Sheet - Ren, Diandong; Leslie, L.; Lynch, Mervyn; Ye, Q. (Moskovskii Gosudarstvennyi Universitet im. M.V. Lomonosova * Fakul'tet Geografii, 2013)
This study projects the sea level contribution from the Greenland ice sheet (GrIS) through to 2100, using a recently developed ice dynamics model forced by atmospheric parameters derived from three different climate models (CGCMs). The geographical pattern of the near-surface ice warming imposes a divergent flow field favoring mass loss through enhanced ice flow. The calculated average mass loss rate during the latter half of the 21st century is ~0.64±0.06 mm/year eustatic sea level rise, which is significantly larger than the IPCC AR4 estimate from surface mass balance. The difference is due largely to the positive feedbacks from reduced ice viscosity and the basal sliding mechanism present in the ice dynamics model. This inter-model, inter-scenario spread adds approximately a 20% uncertainty to the IPCC ice model estimates. The sea level rise is geographically non-uniform and reaches 1.69±0.24 mm/year by 2100 for the northeast coastal region of the United States, amplified by the expected weakening of the Atlantic meridional overturning circulation (AMOC). In contrast to previous estimates, which neglected the GrIS fresh water input, both sides of the North Atlantic Gyre are projected to experience sea level rises. The impacts on a selection of major cities on both sides of the Atlantic and in the Pacific and southern oceans also are assessed. The other ocean basins are found to be less affected than the Atlantic Ocean.